Изменчивость фенетической структуры в городских колониях интродуцированного вида Cepaea hortensis (Gastropoda, Pulmonata) - Сверлова, Н.В. (Інститут зоології ім. І. І. Шмальгаузена НАН України, 2005)
Проанализирована изменчивость фенетической структуры колоний C. hortensis (Muller, 1774) в частично или полностью изолированных городских биотопах Львова. Очевидно, все исследованные колонии образованы потомками относительно небольшого количества особей, первоначально интродуцированных в город. Это объясняет значительное сходство фенетической структуры колоний в разных частях Львова. В то же время, как в соседних колониях C. hortensis, так и в разных частях города зарегистрированы зачатки генетической дифференциации. Генетической и фенетической дифференциации способствуют антропогенные барьеры определенного типа. The variability of the polymorph structure of the colonies of C. hortensis (Muller, 1774) was analysed in partly or completely isolated urban biotopes of Lvov. It is obvious that all the studied colonies were formed by the descendants of the relatively small number of the primary introduced individuals. This explains considerable similarity of the polymorph structure in the different parts of Lvov. At the same time the rudiments of the genetics differentiation were registered both in the neighbouring colonies of C. hortensis and for the different parts of the city. The anthropogenic barriers of definite type are contributing to genetics and polymorph differentiation.